Quasi-duo Partial skew polynomial rings - Cortes, W.; Ferrero, M.; Gobbi, L. (Algebra and Discrete Mathematics, 2011)
In this paper we consider rings R with a partial action α of Z on R. We give necessary and sufficient conditions for partial skew polynomial rings and partial skew Laurent polynomial rings to be quasi-duo rings and in this case we describe the Jacobson radical. Moreover, we give some examples to show that our results are not an easy generalization of the global case.